Perspektif Hukum Ekonomi Syariah Tentang Penyaluran Zakat Maal Yang Dikelola Oleh Badan Amil Zakat Nasional (BAZNAS) Kabupaten Garut - Wati, Ai; Alawiyah, Kiki Rofi'ah (Jurnal Hukum Ekonomi Syariah, 2023)
Zakat is a property that must be issued by every Muslim who is considered capable with several conditions that must be met. In Indonesia, zakat is distributed by the National Amil Zakat Agency. Unfortunately, in the management of zakat maal at the National Amil Zakat Agency of Garut Regency, there are still many proposals for aid applications piling up, so many mustahik have not received zakat. The problem studied is how the mechanism of distributing zakat maal in BAZNAS Garut Regency and how the mechanism of distributing zakat maal in BAZNAS Garut Regency perspective of sharia economic law. The purpose of the study was to find out how the mechanism of distributing zakat maal in BAZNAS Garut Regency and to analyze how the mechanism of distributing zakat maal in BAZNAS Garut Regency perspective of sharia economic law. The method used is field research, namely field research in the form of qualitative research that is descriptive. The research was conducted by conducting direct interviews with BAZNAS staff in an unstructured manner. The results of this study contain that there are five excellent programs in the distribution of zakat maal at BAZNAS Garut Regency, namely Garut Sehat, Garut Taqwa, Garut Peduli, Garut Makmur, and Garut Pintar, which can be distributed after a proposal for assistance that enters BAZNAS to eight asnaf. Even so, the distribution of zakat is not appropriate because it does not meet the principles of Sharia Economic Law, such as justice, tawhid, al-maslahah, and others.